HIGH SCHOOL STUDENTS’ ERROR IN SOLVING WORD PROBLEM OF TRIGONOMETRY BASED ON NEWMAN ERROR HIERARCHICAL MODEL - Thalitha Ariesti Widhia Wardhani; Deshinta P. A. D. Argaswari (IKIP Siliwangi and I-MES, 2022)
This study aims to identify students’ errors in solving word problems of trigonometry according to the Newman Error Hierarchical Model. This study uses qualitative descriptive data gathered based on fact, and data analysis presented descriptively. The population is students of X IPA 2 at SMAN 1 Cikarang Utara, West Java, Indonesia, and to understand more about the error that happened, the researcher took six students of SMAN 1 Cikarang Utara as a sample. The sample is chosen by purposive sampling. Instrument tests, interviews, and documentation are the data collected. This study used the Newman Error Hierarchical Model to analyze high school students’ errors in solving word problems of trigonometry. The results show that students made errors in comprehension, transformation, process skill, and encoding stage. The errors were caused by their lack of understanding some words and terms in the word problem, lack of ability in transforming the word problem to the mathematical model and strategy, lack of processing the algebra and calculation, lack of motivation, and carelessness.